Antarctic subglacial hydrology: current knowledge and future challenges. Issue 6 (13th November 2014) - Ashmore, David W.; Bingham, Robert G.
Abstract: Flood-carved landforms across the deglaciated terrain of Victoria Land, East Antarctica, provide convincing geomorphological evidence for the existence of subglacial drainage networks beneath the Antarctic ice sheet, and motivate research into the inaccessible environment beneath the contemporary ice sheet. Through this research, our understanding of Antarctic subglacial hydrology is steadily building, and this paper presents an overview of the current state of knowledge. The conceptualization of subglacial hydrological behaviour was developed at temperate and Arctic glaciers, and is thus less mature in the Antarctic. Geophysical and remote sensing observations have demonstrated that many subglacial lakes form part of a highly dynamic network of subglacial drainage beneath the Antarctic ice sheet. Recent research into subglacial water flows, other than those directly concerned with lakes, has discovered potentially significant impacts on ice stream dynamics, ice sheet mass balance, and supplies of water to the ocean potentially affecting circulation and nutrient productivity. Despite considerable advances in understanding there remain a number of grand challenges that must be overcome in order to improve our knowledge of these subglacial hydrological processes.